Quality of care indicator performance was minimally changed in 2020 despite the COVID-19 pandemic - Alexander Konson; Michael Kuniavsky; Olga Bronshtein; Nethanel Goldschmidt; Shuli Hanhart; Hannah Mahalla; Shir Peri; Shaul Dollberg; Yaron Niv (BMC, 2022)
Abstract Background In 2020, the COVID-19 pandemic affected healthcare systems throughout the world, including the management of patients and compliance rates of quality indicators. Objective To measure the impact in Israel of the COVID-19 pandemic on the indicator-relevant caseload and compliance rates of the quality indicators reported by medical services providers within the Israeli National Program for Quality Indicators (NPQI). Methods Data was collected from the reports made to the NPQI by participating hospitals and medical service providers. The indicator results for the number of cases and compliance rates for 2019 were compared to those from 2020. We assessed and compared the results of the quality indicators in general hospitals, geriatric hospitals and departments, psychiatric hospitals and departments, emergency medical services (EMS), and Mother and Baby health centers. Results We found a decrease in measurable cases in 2020 relative to 2019, especially in geriatric hospitals. In most indicators, compliance rates rose in 2020. Few indicators had lower compliance rates associated with COVID-19 pandemic regulations. Conclusions and policy implications Routine medical activity decreased in Israel in 2020 in comparison to 2019, as reflected by a decrease in cases, but compliance rates were better in most indicators. The results of our study imply that the functioning of healthcare quality measurement programs should not be interrupted during a pandemic. This not only allows measuring of the healthcare system's performance during a crisis, but also may assist in maintaining a high level of healthcare quality.